Simulation of Flow in Turbopump Vaneless and Vaned Diffusers with Fluid Injection - Ali Ogut; Diego Garcia Pastor (International Journal of Rotating Machinery)
In future space missions by NASA there will be a need for “Space Transfer Vehicles” to perform varying orbital transfers and descents. This requires engines capable of producing different levels of thrust. To accomplish this, the turbopumps employed in these engines should efficiently provide a wide range of flow outputs. However, current fuel and oxidizer turbopumps with vaned diffusers do not perform efficiently at off-design (low) flow rates mainly due to flow separation in the vaned diffuser.